Electrocatalysts: 2D Layered Double Hydroxides for Oxygen Evolution Reaction: From Fundamental Design to Application (Adv. Energy Mater. 17/2019). Issue 17 (2nd May 2019) - Lv, Lin; Yang, Zhaoxi; Chen, Kun; Wang, Chundong; Xiong, Yujie
Abstract : In article number1803358, Chundong Wang, Yujie Xiong and co‐workers review the rational design of layered double hydroxide (LDH)‐based electrocatalysts for use in the oxygen evolution reaction (OER). LDHs exhibit tunable composition and laminated structure, which allow the accommodation of various intercalated anions and possess an elasticity feature similar to "La‐Mian" – one common type of Chinese traditional noodles, thus giving rise to the splendid electrocatalytic performance for the OER.